Arquitetura da (in)segurança: estudando relações entre configuração espacial, artifícios de segurança e violência urbana no bairro Manaíra, João Pessoa, Paraíba - Monteiro, Lia Tavares (2012)
João Pessoa, the capital city of the state of Paraíba (Northeast Brazil), is reputed throughout the country as a quiet place, although it has been acquiring, over the past years, an urban character with social implications similar to those of major metropolitan Brazilian areas. The new situation is evident by the social inequalities, with the creation of confined spaces, which segregate and cause enclosure of the inhabitants, leading to death the public space. This study correlates accessibility in spatial structure with two types of crime data, burglary and robbery, recorded in 2008 and 2009, by the Secretaria de Segurança da Paraíba (The government agency public in charge of safety), in the district of Manaíra, an upper middle class neighborhood, which has, in recent times, been considered one of the most violent areas in João Pessoa. Sought to understand connections between these events and morpho-social aspects of the built environment, where examined the spatial properties, such as accessibility of the urban net, the presence of control measures, the safety of buildings and their uses. Spatial properties were also validated by the observation of pedestrian flows at strategic points of the study area. It was concluded that the presence of intense flows helps to attract potential thieves, physical security and control offers little protection